Opinie nauczycieli szkół specjalnych na temat edukacji włączającej – uczeń ze SPE w szkole włączającej - Chrzanowska , Iwona (Studia Edukacyjne, 2020)
The idea of inclusive education is the concept of education for all. According to opinions of different backgrounds, it seems that the idea of inclusive education in Poland is mainly associated with the “problem” of a presence of students with disabilities in the mainstream school. The studies on the phenomenon of inclusive education were focused on the problems of the organization of education, teachers’ competences, and their consequences for the student with disability. Seldom, if ever, is the phenomenon recognized in the context of all students, participants in the process. The idea of inclusive education goes beyond a single entity, i.e. a student with a disability. This idea requires a search for a new model of school – “a learning school” (like in the model of a learning organization). The school should be a place where people for all time are expanding their capacity to achieve results, constantly discovering and creating the reality in which they live.